Crystals Cd₁₋x ZnxTe – a promising material for non-cryogenic semiconductor detectors: preparations, structure defectness and electrophysical properties - Atroshchenko, L.V.; Galkin, S.N.; Galchinetskii, L.P.; Lalayants, A.I.; Rybalka, I.A.; Ryzhikov, V.D.; Silin, V.I.; Starzhinskii, N.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
Relationship between preparation conditions of the raw charge, crucible material, growth regimes and structure defectness and electrophysical properties of crystals Cd₁₋x ZnxTe has been studied. The crystals were grown both from the raw material which had been pre-synthesized in quartz ampoules and from the raw material synthesized from the elements directly in the growth furnace. It is shown that the best values of electric resistivity ρ (up to 10¹¹ Ohm⋅cm) and sensitivity to X-ray and gamma-radiation are obtained for crystals grown in crucibles of highly pure coal-graphite material from the pre-synthesized raw charge. Correlation has been established between values of ρ and crystal defectness: decrease of dislocation density by 10⁴ times led to 10⁷ times higher values of resistivity.
Concentration of dislocation etching pits regularly decreased with higher purity of the raw material and optimization of crystal preparation technology.